Impact of enhanced recovery on oncological outcomes following minimally invasive surgery for rectal cancer. Issue 7 (12th March 2019) - Quiram, B. J.; Crippa, J.; Grass, F.; Lovely, J. K.; Behm, K. T.; Colibaseanu, D. T.; Merchea, A.; Kelley, S. R.; Harmsen, W. S.; Larson, D. W.
Abstract : Background: Oncological outcomes of locally advanced rectal cancer depend on the quality of surgical and oncological management. Enhanced recovery pathways (ERPs) have yet to be assessed for their oncological impact when used in combination with minimally invasive surgery. This study assessed outcomes with or without an ERP in patients with rectal cancer. Methods: This was a retrospective analysis of all consecutive adult patients who underwent elective minimally invasive surgery for primary rectal adenocarcinoma with curative intent between February 2005 and April 2018. Both laparoscopic and robotic procedures were included. Short‐term morbidity and overall survival were compared between patients treated according to the institutional ERP and those who received conventional care. Results: A total of 600 patients underwent minimally invasive surgery, of whom 320 (53·3 per cent) were treated according to the ERP and 280 (46·7 per cent) received conventional care. ERP was associated with less overall morbidity (34·7 versus 54·3 per cent; P < 0·001). Patients in the ERP group had improved overall survival on univariable (91·4 versus 81·7 per cent at 5 years; hazard ratio (HR) 0·53, 95 per cent c.i. 0·28 to 0·99) but not multivariable (HR 0·78, 0·41 to 1·50) analysis. Multivariable analysis revealed age (HR 1·46, 1·17 to 1·82), male sex (HR 1·98, 1·05 to 3·70) and complications (HR 2·23, 1·30 to 3·83) as independent risk factors for compromised overall survival. Disease‐free survival was comparable for patients who had ERP or conventional treatment (80·5 versus 84·6 per cent at 5 years respectively; P = 0·272). Conclusion: Treatment within an ERP was associated with a lower morbidity risk that may have had a subtle impact on overall but not disease‐specific survival. Abstract : The present investigation aimed to investigate oncological outcomes, comparing enhanced recovery pathway (ERP) versus conventional care by reporting a retrospective analysis of patients undergoing minimally invasive surgery for rectal adenocarcinoma from 2005 to 2018. A total of 600 patients were included in the analysis. The results showed ERP to be associated with a non‐significant improvement in overall survival whereas complications were a main driver for long‐term mortality. Less complications may reduce cancer risk